Evaluation of Drainage System of Light Rapid Transport (LRT) Depo – Kelapa Gading – Jakarta City - Joko Nugroho; Mohammad Bagus Adityawan; Ana Nurganah Chaidar; Yadi Suryadi (Journal of Engineering and Technological Sciences, 2023)
LRT Depo is a vital infrastructure in the operation of Jakarta’s LRT system. The LRT Depo is located in the Kelapa Gading area. Kelapa Gading is an inundation-prone area in Jakarta. Hence a drainage system should be prepared to manage surface runoff in the area to avoid additional runoff to the surrounding drainage system. In order to reduce runoff in Jakarta Special Province, the Governor of Jakarta has imposed a regulation on surface runoff management for every developed area. The runoff control measures, promoted in the regulation to be applied, are in the form of infiltration wells and storage ponds. The principle of reducing peak discharge by a possible storage system for LRT Depo was designed and applied to comply with regional regulations on rainwater control. The drainage system, initially based on the regulations, was also modeled in the Storm Water Management Modelling software (SWMM). This study evaluated the drainage system by elaborating the reduction of the peak discharge based on the simulation. A reduction of peak discharge was observed in the modeling results. The proposed runoff control at LRT Depo Kelapa Gading is a proper design of infrastructure development for a flood prone area.